2006
DOI: 10.1007/s00464-005-0771-8
|View full text |Cite
|
Sign up to set email alerts
|

Telerobotic surgery for right and sigmoid colectomies: 30 consecutive cases

Abstract: The 30 consecutive cases demonstrated the technical feasibility of using the DaVinci system for a colectomy. The longevity of the DaVinci system's use for colectomy will be determined by comparison of its cost and outcomes with those for conventional laparoscopic colectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 13 publications
9
57
1
3
Order By: Relevance
“…As we gain more experience, we expect the operating time to fall even further and be similar to the open method. The advanced technology in the robotic surgical system shortens the time of actual operative procedure itself, because it mimics intuitively the open procedure as opposed to the laparoscopic procedure in which surgical maneuvering is counterintuitive [4,5] The estimated blood loss was significantly less in roboticassisted surgery compared with the open method (165.14 vs 406.04 ml). Magnified vision and improved dexterity helps in better vascular control than the open method.…”
Section: Discussionmentioning
confidence: 99%
“…As we gain more experience, we expect the operating time to fall even further and be similar to the open method. The advanced technology in the robotic surgical system shortens the time of actual operative procedure itself, because it mimics intuitively the open procedure as opposed to the laparoscopic procedure in which surgical maneuvering is counterintuitive [4,5] The estimated blood loss was significantly less in roboticassisted surgery compared with the open method (165.14 vs 406.04 ml). Magnified vision and improved dexterity helps in better vascular control than the open method.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of patients undergoing this procedure was 49 years (range 19-68 years). The mean hospital stay was 6 days (range 4-13 days), while the mean BMI was 27.3 (range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The mean operative time was 166 min (range 60-270 min).…”
Section: Resultsmentioning
confidence: 99%
“…Early experiences with different robotic-assisted colorectal procedures such as colectomies (Rawlings et al, 2006;D'Annibale et al, 2004), rectopexy (Munz et al, 2004) and anterior resections (D'Annibale et al, 2004 are described in recent literature including our previous early report of robotic-assisted TMEs (Pigazzi et al, 2006). These studies found no difference in specimen length, number of lymph nodes retrieved, estimated blood loss, recovery of bowel function or hospital stay between laparoscopic and robotic colorectal resections.…”
Section: Discussionmentioning
confidence: 99%